2002
DOI: 10.1074/jbc.m205348200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Functional Expression, and Tissue Distribution of a Novel Human Gap Junction-forming Protein, Connexin-31.9

Abstract: A novel human connexin gene (GJA11) was cloned from a genomic library. The open reading frame encoded a hypothetical protein of 294 amino acid residues with a predicted molecular mass of 31,933, hence referred to as connexin-31.9 (Cx31.9) or ␣11 connexin. A clone in GenBank TM containing the Cx31.9 gene localized to chromosome 17q21.2. Northern analysis of Cx31.9 showed a major 4.4-kilobase transcript, which was expressed at varying levels in all tissues analyzed. Two monoclonal antibodies generated against di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 42 publications
0
74
0
Order By: Relevance
“…Gap junction channels of the human orthologue Cx31.9 also exhibit low unitary conductance (38,39). Thus, its effect on conduction characteristics in human cardiac electrophysiology and AV-nodal physiology should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Gap junction channels of the human orthologue Cx31.9 also exhibit low unitary conductance (38,39). Thus, its effect on conduction characteristics in human cardiac electrophysiology and AV-nodal physiology should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mutation may disrupt a binding interaction that involves the tip of the C-terminus. Several connexins have been shown to interact with proteins via the C-terminal domains [13,21,32,33,45], with the scaffolding protein ZO1 being the most prevalent partner. Indeed Cx36 has recently been found to interact with ZO1 at this site [24].…”
Section: Discussionmentioning
confidence: 99%
“…1). Previously, investigators had shown that Cx30.2 gap junction channels exhibit little gating sensitivity to transjunctional voltage [9][10][11]. The insensitivity or activation of Cx30.2 G j at high V j may be important for the preservation of slow impulse propagation through the atriventricular node.…”
mentioning
confidence: 99%
“…Recently, another cardiac connexin, mouse Cx30.2 (human Cx31.9) was discovered [9][10][11]. Cx30.2 expression was detected within the sinoatrial and atrioventricular nodes [11,12].…”
mentioning
confidence: 99%